Pengembangan Desain Poster Edukasi Ekologi sebagai Upaya Meningkatkan Wawasan Lingkungan Wisatawan Hutan Mangrove Karangsong Kabupaten Indramayu - Putri, Dian Permana; Kurniawan, Dede Trie (Universitas Sebelas Maret, 2017)
The aim of this research is to arrange the design of educative poster which is ideal to the tourist level of knowledge Karangsong Mangrove forest tourism area. Based on the judgment of educative poster design of mangrove forest, the expert of ecotourism and knowing the effectiveness level of educative poster design to the tourist level of knowledge to Kangrangsong mangrove forest area. The poster design developed by using adobe software and completed with video by using flash macromedia to support the poster, while for judgment of the design of educative media is by using evaluation questionnaire given to 3 ecotourism experts and for knowing the effectiveness level of educative media is by using questionnaire. The result of judgment shows that educative poster media and video are feasible to be tested and revised as suggestion. While the result of questionnaire shows that developing poster and video are effective to the tourist level of knowledge with the percentage 97.1%